2002
DOI: 10.1097/00125817-200209000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Effects of risk counseling on interest in breast cancer genetic testing for lower risk women

Abstract: Purpose: A randomized trial was conducted to test the effects of two counseling methods (genetic counseling and group counseling) against a control no-intervention condition on interest in genetic testing in lower risk women.Methods: After completing baseline surveys, women (N ϭ 357) were randomized to one of three conditions: to receive individual genetic risk counseling, to receive a group psychosocial group counseling, or to serve as a control group. Participants completed follow-up questionnaires 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 15 publications
3
39
1
Order By: Relevance
“…However, the populations examined in these studies were different from ours: most women in three of the studies had a low or moderate risk of breast cancer, whereas women in our study were mainly high risk [15,31,32]. In the fourth study, Green et al [17] showed that education and counselling increased knowledge and reduced inclination to undergo testing in low risk, but not high risk women.…”
Section: Discussioncontrasting
confidence: 60%
“…However, the populations examined in these studies were different from ours: most women in three of the studies had a low or moderate risk of breast cancer, whereas women in our study were mainly high risk [15,31,32]. In the fourth study, Green et al [17] showed that education and counselling increased knowledge and reduced inclination to undergo testing in low risk, but not high risk women.…”
Section: Discussioncontrasting
confidence: 60%
“…Gaps in understanding may lead to ineffective genetic counseling and health promotion communication derived from focus on a specific disease and links to human genetics. Evidence supports the conclusion that lay audiences who overestimate the genetic contribution to health make less personal effort to control modifiable cofactors of disease, while underestimation contributes to frustration in the face of failure to control health processes and outcomes (Bowen, Burke, Yasui, McTiernan, & McLeran, 2002). To increase the heuristic value of problematic integration theory, situations such as the one described afford important contexts in which to assess the meaning of uncertainty.…”
Section: Micro-versus Macroillness Causation Beliefsmentioning
confidence: 77%
“…We based the content of this intervention on the self-regulation model developed by Leventhal and colleagues [35] applied to women at risk for breast cancer [4, 5, 36]. The self-regulation model of health behavior addresses health risk communications and the use and effects of health screening.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Mixed-risk women either had reported a specific mixed-risk factor for breast cancer or reported a cancer worry score of 8 or over. We used the data in our previous research to determine a “high” worry score, indicating women who might need more intensive assistance [4, 5]. Genetically at risk women had a relatively high family history of breast cancer suggestive of possible positive genetic mutation status [37, 38].…”
Section: Experimental Methodsmentioning
confidence: 99%